Human Capital in Society’s Sustainability Significance - Toshpulatov Isroyiljon Ismoilovich (Periodica Journal, 2023)
This article reveals the importance of human capital, which is considered the main indicator of stability in modern societies. This serves to increase general processes such as economic development, information society, innovative culture, and political pluralism. The socio-philosophical factors that the stability of society depends on the stable development of human capital have been scientifically analyzed.
Keywords: human; Society; capital